Bibliometric Trends of Science, Technology, Engineering, Mathematic Integration and Science Process Skills Development through Sustainable Seed Paper for SDGs - Nensy Eka Selviana; Endang Susantini; Lidya Vriska Fatimah Azzahra; Muhammad Zahrudin Afnan; Rinaldiyanti Rukmana; Erti Hamimi (Universitas Syiah Kuala, 2026)
This research examines the incorporation of scientific process skills within science, technology, engineering, and mathematic (STEM) education, focusing particularly on sustainability and the insufficient alignment among teaching methodologies, skill enhancement, and eco-friendly educational resources. A mixed-methods approach was utilized, integrating bibliometric analysis with a systematic literature review to uncover publication trends, key themes, and research deficiencies in STEM education, scientific process skills, and sustainability. Data were collected from the Scopus database using the search terms